Implementasi Budaya Jabat Tangan Dalam Pembentukan Sikap Hormat Siswa - Moh Wardi; Aisyah Amini Mansur; Nailah Aka Kusuma (Cendekia, 2023)
This study aims to explore in depth the Mushafahah program in daily activities at Madrasah Ibtidaiyah Al Ghazali Rombasan Pragaan Sumenep. This study used a descriptive qualitative approach with interview, observation, and documentation methods. The analysis was carried out on a single case at Madrasah Ibtidaiyah Al Ghazali, a reflection of Pragaan Sumenep with the method introduced by Miles and Huberman which consisted of data collection, data reduction, data presentation, and verification. The results of the study show that the habit of shaking hands contributes to increasing students' respect for teachers in the madrasah environment and outside the madrasa. This can be proven when students are used to greeting and shaking hands when meeting teachers, speaking politely, and listening when the teacher explains